To Identify Buyer Behavior Towards Online Shopping Due to Covid-19 Pandemic in Hong Kong - Lio, Cheng Tong (University of Saint Joseph, 2022)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The management styles in transitions in South Korea - Chiu, Ien Lon (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

The influence of bilateral trade agreements on mode of market entry choice of resources seeking Chinese firms operating in Nigeria - Olukayode, Iwaloye Ojo (University of Saint Joseph, 2014)
In the past three decades there have being an increase in the number of Bilateral Trade Agreements (BTAs) globally. These agreements involve huge human and financial movements and are essentially based on trade and investment. This phenomenon has brought new dimension to global business environment by changing the landscape in whichfirms from emerging markets operate in another emerging market. In the light of this, this dissertation is to examine how bilateral trade agreementsprovisions influence choice of foreign market entry mode of resource seeking Chinese Multinational Enterprises operating in Nigeria. This study adopts a qualitative design, collecting data using semi-structured interviews. The data are analyzed with content analysis and explanation building to identify themes through application of replication logic. The data obtained from the interviews regarding the research questions are presented and discussed as major findings and adoptedfor the creation of the new model for the study of resources seeking firm’s choice of market entry modes in emerging markets The model developed in this dissertation makes a contribution to theory for the study of market entry modes of MNEs from developing countries entering another developing country. In this case, Chinese resources seeking multinational firms entering Nigeria. Elements of Dunning’s OLI theory, Resources Dependency Theory, and Institution theory extended for the purpose for the theory development process. This investigation also provides important information to assist state policy actors in their development of bilateral trade agreements between China and Nigeria. Implications for firms and their involvement in developing countries and with framework where bilateral trade agreements exist are also provided
Keywords: PhD in Business Administration (D-BA); Thesis and Dissertations; University of Saint Joseph

Study on the managerial style change in Australia - Tang, Pou I. (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Study on management style changes in Germany - Chau, Manuel (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Perspectives on management styles in Japan - Melo, Hugo Hermano Brum de (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Modelling the influence of mobile information and communication technologies on the festival tourism experience - Silva, Manuel Vasconcelos Ferreira Correia da (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management styles transitions in China - Branco, Ivânio dos Santos (University of Saint Joseph, 2009)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management style in United Kingdom - Sun, Lam (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management style change: a Singapore prespective - Antunes, João Maria Nolasco Lamas Costa (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Management issues in Hong Kong - Iun, Mio Hong (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

German restaurant adoption in Macau - Loi, Sio Mei (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management transition in the United States - Choi, Hoi Lam (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management transition in South Korea - Chan, Wai Ip (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management style change in France - Ng, Sut Fan (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Exploratory study of management change in Egypt - Chan, Wai Kei (University of Saint Joseph, 2011)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Development of management style in Taiwan - Jung, Iok Fan (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Developing an understanding of Yoox Net-A-Porter Group's business model - Brito, Clara Susana Pereira Soeiro de (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Business plan: pure prawn - Chong, Mao Lou (University of Saint Joseph, 2013)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Asian business: a study of Indian business management styles - Un, Man Long (University of Saint Joseph, 2010)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study on management style changes in Vietnam - Chan, Im Fan (University of Saint Joseph, 2012)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study on effective retention of human resources in the Macau gaming industry - U, Chin Hong (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An Exploratory Study of Factors Influencing the Consumer Behaviour of Macau Chinese Millennial Women in their Purchasing on Taobao - Tong, Ka Wai (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

An exploratory study into understanding the marketing mix strategy of green fast-moving consumer goods - Pangan, Maria Rebeca Aquino (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study on the consumer market for dietary supplements in Macau - De La Cruz Y Lin, Lisa (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study on customer loyalty and Japanese Ramen specialty restaurant - Leong, Tek Kei (University of Saint Joseph, 2018)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A study of Tissot Group's marketing strategy in Macau - Mou, Hio Fong (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph